Cancer Stem Cell Hierarchy in Glioblastoma Multiforme - Bradshaw, Amy; Wickremsekera, Agadha; Tan, Swee T.; Peng, Lifeng; Davis, Paul F.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Glioblastoma multiforme (GBM), an aggressive tumor that typically exhibits treatment failure with high mortality rates, is associated with the presence of cancer stem cells (CSCs) within the tumor. CSCs possess the ability for perpetual self-renewal and proliferation, producing downstream progenitor cells that drive tumor growth. Studies of many cancer types have identified CSCs using specific markers, but it is still unclear as to where in the stem cell hierarchy these markers fall. This is compounded further by the presence of multiple GBM and glioblastoma cancer stem cell subtypes, making investigation and establishment of a universal treatment difficult. This review examines the current knowledge on the CSC markers SALL4, OCT-4, SOX2, STAT3, NANOG, c-Myc, KLF4, CD133, CD44, nestin, and glial fibrillary acidic protein, specifically focusing on their use and validity in GBM research and how they may be utilized for investigations into GBM’s cancer biology.